Faktor Self Service Technology Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Masalalu Cafe, Rawa Domba - B Syariffudin Latif; Khoirotunnisa Nur Priyanti (Pusat Riset dan Inovasi Nasional, 2024)
The study aims to analyze the self-service technology and service quality factors of customer satisfaction at Masalalu Cafe, Rawa Domba, Jakarta. The sample used in this study uses primary data collected through questionnaires distributed to 94 respondents. Data analysis techniques use quantitative descriptive analysis. The results of the research are self-service technology and quality of service-generating data that have a positive combined and significant impact on customer satisfaction at Masalalu Cafe